Key Advantages of Digital Learning in Group Decision Support System: Benefit Evaluation and Its Perspective - Shu-Chin Huang; Hung-Yu Lin; Yi-Chang Chen; Chih-Wen Hsiao (Engineering Proceedings)
In today’s dynamic business landscape, companies need to enhance problem-solving efficiency to produce products or services to meet evolving customer needs. Fostering creative talent and utilizing Group Decision Support Systems (GDSS) have become crucial in the management of human resources and marketing. While empirical studies demonstrate the positive impact of GDSS on learning, a gap exists in understanding its correlation with outcomes like enhanced creativity. Thus, qualitative research is needed to uncover the cognitive processes for favorable results with the adoption of GDSS. We explored the relationship between Project-Based Learning (PBL), GDSS deployment, and outcomes in a cross-organizational study. Results highlighted PBL activities facilitated by GDSS and the key benefits of digital learning, and managerial and academic considerations were proposed.